Metáfora discursiva crítica: relatos de mulheres violentadas - Rocha, Daniela Cynthia de Sá (2023)
Violence against women is a practice that has been historically and culturally established in society and continues to resonate in contemporary times through various types of aggression and misogynistic, patriarchal discourses that permeate social practices, thereby asymmetrically positioning men and women in terms of power. Women are fighting for empowerment and equality, seeking social change. Our general objective is to analyze accounts of women who have experienced violence, particularly psychological violence, as a critical discursive metaphor. The main theoretical bases for this study are Lakoff and Johnson (2002), Charteris-Black (2004, 2006), and Vereza (2010, 2017). Thus, the bias of this research is based on Critical Discourse Analysis (CDA) studies by Chouliaraki and Fairclough (1999), Fairclough (2001, 2003, 2010), and Magalhães (2017), observing the maintenance of violence against women as a social practice in contemporary times and the counter-hegemonic perspective of the feminist struggle for social change through language. This aligns with current sociodiscursive-interactional textual linguistics studies (Koch, 1999, 2002, 2009; Marcuschi, 2008; Mondada and Dubois, 2003) and the sociocultural interactions proposed by Van Dijk (2002, 2012, 2017), bringing a study of a metaphor guided by discourse as a predominant element in the (re)construction of meanings related to aggression against women. The following questions will guide our work: i) how are critical discursive metaphors conceived?; ii) why shed light on a type of metaphor to elucidate violence, particularly psychological violence, against women?; iii) what non-discursive elements contribute to the analysis of this type of metaphor? The specific objectives are: i) to bring to light a type of metaphor guided by discourse, the critical discursive metaphor; ii) to reveal how accounts are configured as critical discursive metaphors of violence against women; iii) to analyze accounts based on contextual, discursive, and cultural factors; iv) to extract potential for promoting social change from the analyses. The hypothesis is centered on verifying that the accounts themselves serve as a place of violence, as this textual genre plays a relevant social role when victims of violence publicly present scenes of the abuse they have suffered, serving as a mirror for other women who recognize themselves in situations of continuous abuse, building a largescale support network to eliminate the syndrome of "small power" in which men have more power and women have less (ESPÍNOLA, 2018). Methodologically, we adopt a linguistics approach by collecting accounts from anonymous followers on the public Instagram page @maselenuncamebateu over the course of one year (2020). This approach is relevant because our justification asserts the thematic relevance of psychological violence as a hidden, disguised, and invisible form of violence, as studied by Hirigoyen (2006) and Schwab and Meireles (2017). Thus, the results of our analyses provide a clearer understanding of psychological violence; they highlight accounts of women who have experienced violence as echoes of patriarchal society, sexism, and misogyny that maintain hegemonic power in the hands of aggressors; and they also demonstrate that such accounts are linguistic tools used to end power asymmetry between men and women.